HUBUNGAN PENGETAHUAN DENGAN PERILAKU BIDAN DALAM PELAKSANAAN INISIASI MENYUSU DINI (IMD) PADA IBU BERSALIN DI WILAYAH KOTA BOGOR: Elin Supliyani *), dan Maya Astuti **) Alamat : Program Studi Kebidanan Bogor, Jl. Dr.Sumeru No.116 Bogor Email : elinsupliyani@yahoo.co.id - Elin Supliyani; Maya Astuti (Poltekkes Kemenkes Bandung, 2017)
Rate of Infant mortality in the city of Bogor which is 26 per 1000 newborn is the highest in West Java. Early initiation of breastfeeding or breast feeding directly on the newborn, can prevent child deaths. Not all midwives carry out the Initiation of Early Breastfeeding, it is strongly influenced by the knowledge of midwives which is have impact on the behavior of midwives in implementing the IMD. The research objective was to determine the relationship between knowledge of the behavior of private midwifery practices in the implementation of the IMD in mothers birthing in the city of Bogor. This study is an analytical research which had a Crosssectional approach where the independent variable is knowledge of midwives, while the dependent variable is the behavior of midwives in the implementation of the IMD. The questionnaire is the research instruments to measure the knowledge of midwive, and observation sheet is used to measure the behavior. The 96 respondents in this study were midwive private practice are taken proportional random sampling. Analysis method used was chi square. The majority (66.7%) of respondents have good knowledge, 64.6% already have Early Initiation of Breastfeeding and the statistical tests showed there is no relationship between knowledge of the behavior of midwives in the implementation of the IMD program, where the value (p> 0.05). Department of Health and professional organizations need to increase midwives’s knowledge of IMD by conducting refreshertraining through seminars APN updates or IMD. Midwifery education need more emphasis to students on learning materials in the IMD.